Food Hoarding Intention during Covid-19 in Indonesia: the Role of Government Regulation as Moderating Variable - Kristiningsih Kristiningsih; Santirianingrum Soebandhi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2022)
The outbreak of Covid-19 in early 2020 has raised public anxiety because of the uncertainty about the impact of this outbreak. At the beginning of this outbreak, we often encountered unusual purchasing behavior. One of them is by hoarding food or buying basic needs in large quantities in anticipation of the possible impacts during the Covid-19 pandemic. Therefore, this study aims to analyze the effect of risk perception and the three components of Theory of Planned Behavior (TPB), namely: attitudes, subjective norms, and perceived behavioral control on individual intentions to hoard basic needs in order to understand individual responses to pandemic conditions. This study also adds government regulations related to Large-Scale Social Restrictions (PSBB) as a moderating variable. This study involved 194 respondents. The data obtained were then processed using the PLS-SEM method. The findings of this study indicate that food hoarding intention is influenced by risk perception and the three TPB components. Meanwhile, PSBB did not moderate the relationship between the three TPB components on food hoarding intention.